Increased snow accumulation reduces survival and growth in dominant mat-forming arctic-alpine lichens. (3rd May 2016) - BIDUSSI, Massimo; SOLHAUG, Knut Asbjørn; GAUSLAA, Yngvar
Abstract: Relative growth rates (RGR) and carbon-based secondary compounds (CBSCs) were quantified in four dominant terricolous arctic-alpine mat-forming lichens with different preferences for snow cover. The aim was to evaluate the effects of snow depth, and thus snow cover duration, on lichen growth and performance. The species, Alectoria ochroleuca, Flavocetraria nivalis, Cladonia mitis and Cetrariella delisei, are associated with increasing snow depth, respectively. They were transplanted for one year at five snow depths (0, 60, 120, 160 and 200 cm measured in early May) along each of four natural ridge to snow bed gradient transects in oceanic-alpine sites (western Norway). Snow slightly thicker than in source habitats caused negative RGR in the ridge top-dependent A. ochroleuca and the co-occurring F. nivalis with somewhat higher snow tolerance. Only C. mitis with the broadest ecological niche had positive RGR along most of the gradients (0–160 cm), even outside its natural range. The most snow-tolerant species, C. delisei, tolerant also to temporal inundation in water, had the lowest RGR. Nevertheless, it performed as well in places with little or no snow as in places where it grows naturally. Snow depth significantly affected total concentrations of CBSCs mainly in A. ochroleuca, which experienced substantial mass loss under snow. There was a highly significant increase in usnic acid concentration with increasing mass loss in A. ochroleuca, probably because usnic acid decays more slowly than other components. In conclusion, snow reduced lichen RGR, but in species-specific ways. Therefore, increasing snow depth per se along spatial and/or temporal scales likely reduces abundance and distribution of dominant mat-forming lichens in the alpine ecosystems of Scandinavia.